The Primacy of the Perceptual Experience in Maurice Merleau-Ponty - Ballabio, Alessandro (Revista VIS: Revista do Programa de Pós-Graduação em Artes Visuais, 2017)
Le primat de la perception et ses conséquences philosophiques (1946) is the transcription of the discussion that Merleau-Ponty had on November 23, 1946, at the Société française de Philosophie on the results of Phénoménologie de la perception (1945). Merleau-Ponty states that perception is not an intellectual but a practical synthesis that implies the movement of the body, as the origin of the perceptual experience of the world.